Uso de las competencias lingüísticas y su aporte en el aprendizaje del idioma inglés en estudiantes del segundo año de bachillerato de la unidad educativa del milenio “Simón Bolívar” parroquia Pimocha, cantón Babahoyo, provincia los Ríos, periodo lectivo 2017-2018”. - Zúñiga Carpio, Jairo Abelardo (2017)
The present research work has the purpose to disclose information about linguistic competences and as using them in a correct way to improve the academic performance, the English language is important in the educational, social and cultural area since it uses as tool to develop abilities, skills, attitudes, aptitudes and competences. The limited level of knowledge about the linguistic competences in students causes a low level of comprehension, analysis, and expression. The research is exploratory, descriptive and field level; so that one was present at the place where the above mentioned problematic happens, for what it raises as purpose to reach to the improvement of the education. Once the problem was identified, there was developed the theoretical frame, the methodology of investigation, the instruments to using for the compilation, analysis and interpretation of statistical information, In addition conclusions and recommendations were obtained by the intention of focusing towards the elaboration of the didactic proposal. The raised proposal is constituted by objectives and activities with which the students with the help of the teacher manages to develop their abilities, skills, attitudes, aptitudes, the same ones that they allow their to improve favorably in their academic performance and their social relations.